2004
DOI: 10.1097/00124784-200407000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Critical Issues in Bioterrorism Preparedness

Abstract: The Bioterrorism Preparedness and Response Survey (BPRS) was a survey of Ohio local health departments' capacity to respond to bioterrorism. Soon after completion of the BPRS, the events of September 11 occurred, followed by the human cases of anthrax. The Ohio Response to Bioterrorism 2001 Survey (ORB) identified bioterrorism preparedness issues related to the suspected anthrax incidents. The BPRS measured capacity before September 11, 2001, and the ORB measured Ohio communities' response to white powder inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 1 publication
0
9
0
1
Order By: Relevance
“…If the aims of the study are well defined, and the selection criteria have taken in all the specific disease/vector characteristics, setting up a sentinel unit as a targeted disease monitoring tool can be very successful. To date, sentinel herd surveillance has been used for a variety of purposes such as monitoring for the presence of new or re-emerging diseases, surveying anti-microbial resistance and even as a method to prevent bio-terrorism (Brannen et al, 2004). It is important to stress, however, that the successful use of sentinel herd surveillance depends on the precision of targeting a disease/vector, which inevitably depends on the availability and correct interpretation of epidemiological knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…If the aims of the study are well defined, and the selection criteria have taken in all the specific disease/vector characteristics, setting up a sentinel unit as a targeted disease monitoring tool can be very successful. To date, sentinel herd surveillance has been used for a variety of purposes such as monitoring for the presence of new or re-emerging diseases, surveying anti-microbial resistance and even as a method to prevent bio-terrorism (Brannen et al, 2004). It is important to stress, however, that the successful use of sentinel herd surveillance depends on the precision of targeting a disease/vector, which inevitably depends on the availability and correct interpretation of epidemiological knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Any setbacks that occurred as a result of the bioterrorist attack are restored and lessons learned in this phase are incorporated in future preparedness plans toward a bioterrorism attack (Brannen & Stanley, 2004; Das & Kataria, 2010). Any damage done to the public health facilities and the essential items utilized during the response phase are replenished (Das & Kataria, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the literature examined, Brannen and Stanley 38 were the only researchers who assessed training specific to bioterrorism surveillance. Quality of training was not assessed; rather, all 138 health departments in the state of Ohio indicated that an average of 3.3 staff members per health department were trained in surveillance.…”
Section: Education and Training Needs For Bioterrorism Surveillancementioning
confidence: 99%
“…Quality of training was not assessed; rather, all 138 health departments in the state of Ohio indicated that an average of 3.3 staff members per health department were trained in surveillance. 38 None of the examined studies attempted to determine the type of training needed related to using automated electronic syndromic surveillance systems. Most acknowledged that enhanced computer support was needed for users of electronic systems.…”
Section: Education and Training Needs For Bioterrorism Surveillancementioning
confidence: 99%